Tea Bag Biji Alpukat (Persea Americana Mill) terhadap Kadar Gula Darah Tikus Putih (Rattus Norvegicus) - Ida Eliza; Erlin Yustin Tatontos; Rohmi Rohmi; Yunan Jiwintarum (Quality : Jurnal Kesehatan, 2017)
ABSTRACT Blood sugar levels are a very important factor for body activity because blood sugar is the main energy source whose metabolism is liver. High blood sugar levels are called hyperglycemic conditions. The hyperglycemic state is a symptom of diabetes mellitus. Diabetes mellitus is a problem that is often found in Indonesian society. This disease can cause microvascular and macrovascular complications. Giving traditional medicine such as avocado seeds (P. americana Mill) in the form of tea bag is expected to reduce the level of blood sugar. Objective: To find out the effect of avocado seeds (P. americana Mill.) In the form of tea bag on blood sugar levels of white mice (R. norvegicus) wistar strains that are hyperglycemic Method: This study is a Pre-experiment research with a Pretest-One Group research design Posttes, using 6 rats aged two to four months. After a week of adaptation and successfully induced with alloxan, a pretest blood sugar level was tested at the time. The treatment was given for one week and posttest blood glucose levels were examined. Results: The study showed a mean blood sugar level of hyperglycemic wistar white rats before being given avocado seeds (P. americana Mill.) In the form of tea bag 226.4 and average after being given avocado seeds (P. americana Mill.) In the form tea bag is 154 mg / dL. Conclusion: Avocado seeds (P. americana Mill) in the form of tea bag have an influence on the decrease in blood sugar levels of white rats (R. norvegicus) hyperglycemic wistar strains Keywords: Avocado Seeds, Hyperglycemic, Blood Sugar Levels, Tea Bag